Phylogenetic Signal Dissection of Heterogeneous 28S and 16S rRNA Genes in Spinicaudata (Branchiopoda, Diplostraca) - Xiaoyan Sun (MDPI AG, 2021)
It is still a challenge to reconstruct the deep phylogenetic relationships within spinicaudatans, and there are several different competing hypotheses regarding the interrelationships among Eocyzicidae, Cyzicidae s. s., Leptestheriidae, and Limnadiidae of the Suborder Spinicaudata. In order to explore the source of the inconsistencies, we focus on the sequence variation and the structure model of two rRNA genes based on extensive taxa sampling. The comparative sequence analysis revealed heterogeneity across species and the existence of conserved motifs in all spinicaudatan species. The level of intraspecific heterogeneity differed among species, which suggested that some species might have undergone a relaxed concerted evolution with respect to the 28S rRNA gene. The Bayesian analyses were performed on nuclear (28S rRNA, EF1α) and mitochondrial (16S rRNA, COI) genes. Further, we investigated compositional heterogeneity between lineages and assessed the potential for phylogenetic noise compared to signal in the combined data set. Reducing the non-phylogenetic signals and application of optimal rRNA model recovered a topology congruent with inference from the transcriptome data, whereby Limnadiidae was placed as a sister group to Leptestheriidae + Eocyzicidae with high support (topology I). Tests of alternative hypotheses provided implicit support for four competing topologies, and topology I was the best.